Covid-19 And Its Impact on Strategic Management Using the Balance Score Card Method in Bus Companies in Slovakia - Eva KICOVA; Olga PONISCIAKOVA (Communications of International Proceedings, 2022)
The Covid-19 pandemic has affected all areas of the global economy. In the public transport sector, it has caused a huge decrease in passenger mobility, which logically has an impact on the functioning of companies operating in the tertiary sector of the national economy. In Slovakia, there was a 60% decrease in transported persons. The Covid-19 pandemic has also taken its toll on overall employment in the sector as well as income. Following this, the main emphasis will be on the strategic management of the company and its importance. In this paper, we present the results of a survey focused on the use of modern strategic management tools, including the BSC methodology in companies in the Slovak Republic. The BSC system is a tool that is commonly used in the strategic management of developed countries, which is why we will propose a methodology for the BSC system that can be used in the strategic management of bus transport companies. We will suggest areas that need to be monitored in selected 4 perspectives of the BSC system with regard to the specifics of bus transport.
Keywords: Balance Score Card; Strategic Management; The Bus Transport Companies